Comparative Study between Analytical Method and Finite Element Method of a Cylindrical Bore Journal Bearing Behaviour - Nuruzzaman, Dewan Muhammad (1998)
This thesis describes a comparative study between analytical method and finite element method of a cylindrical bore journal bearing behaviour. In calculating the performance characteristics of a journal bearing such as pressure distribution, load capacity, flow requirement and power loss, isothermal analysis was carried out. Using both analytical method and finite element method, the effects of variations in operating variables such as eccentricity ratio and shaft speed on the bearing design parameters were calculated. With regard to CPU time, analytical method performs better than finite element method; but in terms of obtained results, finite element method shows better performance than analytical method. The analytical results and finite element results are compared. In order to check the validity, when these results are compared with the available published results, on the whole, finite element results show better agreement than analytical results.